Building Design and Performance Test of Vibration Beds with Whole Body Vibration - Desak Ketut Indrasari Utami (Journal of Global Pharma Technology, 2018)
Introduction: Vibration is a mechanical motion that oscillates around a fixed point. Whole Body Vibration (WBV) can be defined as vibrations that pass through the surface, backrest, or the floor, either in standing or reclining position. WBV has been proved to lower the level of awakening, inducing sleepiness by providing sense of comfort, and improving insomnia. This study aims to construct a bed with Whole Body Vibration (WBV) which was expected to provide comfort, lowering sleep onset, as well as inducing sound sleep, thus becoming a non-pharmacological treatment option for sleep disorders. Method: This study was conducted in two stages which began with designing and manufacturing of the vibration bed and followed by a performance test. Assesment was conducted based on subjective interviews. Performance test results were presented descriptively. Result: According to the functionality testing, the vibration bed could produce vibration frequency between 1-4 Hertz and displacement 0.094-0.397 mm on vertically directed vibration. According to performance test, as many as 94.1% of subject’s preferred 1 Hertz frequency compared to other frequencies. Furthermore, 88.23% felt comfortable using the vibration bed, 76.47% experienced improvement in onset of sleep and also more soundly sleep. There were only 23.52% of subjects that experienced no change from previous sleep pattern. No side effects were found during the performance test. Conclusion: Lower frequency Whole Body Vibration (WBV) bed with vertical vibration effectively enhanced the subjects’ sense of comfort and improved sleep quality with no observed side effect.Keywords: Whole Body Vibration, Vibrating bed design, Insomnia, Performance test.